The role of diffusion-weighted imaging in the diagnosis of early kidney damage - Kavak, Şeyhmus (The European Research Journal, 2023)
Objective: This study aimed to determine a threshold value for distinguishing early-stage chronic kidney disease (CKD) from moderate and advanced stages as well as patients with early-stage CKD from those with normal renal function using apparent diffusion coefficient (ADC) and normalized ADC values. Methods: This retrospective study enrolled 257 patients. Diffusion-weighted images were obtained with a set of b = 50,400,800 values. In each patient, six ADC values were measured from upper, middle, and lower areas of both kidneys, and three ADC values were measured from the spleen. Patients with CKD were classified into five subgroups and healthy patients were classified into two subgroups according to their glomerular filtration rate (GFR). Results: The renal ADC values were found to be positively correlated with GFR (r = 0.790, p < 0.001) and negatively correlated with creatinine levels (r = −0.709, p < 0.001). The mean ADC values of the stage 1 and 2 CKD groups were found to be significantly higher than those of advanced-stage CKD groups (p < 0.001), and these values were significantly lower in the stage 1 and 2 CKD groups than in the healthy group (p < 0.001). With a cut-off value of ≥1.791 for ADC, the sensitivity was 76.5% and the specificity was 85% while distinguishing between patients with early- and advanced-stage CKD. Conclusion: Renal and normalized ADC values are strongly correlated with CKD stages, and with the use of appropriate threshold values, the difference between early and advanced stages of CKD can be predicted.